The development of environmental management culture in high school students in non-formal education with a cultural and ecological focus - Demidova, Natalia N. (2020)
The purpose of the article is to develop the educational paradigm of the culture of environmental management for advanced education aimed at sustainable development. The methodological foundations of the research are established, presented by cultural-ecological, axiological, personal-activity, integral-situational methodological approaches. The key research methods are defined: system-structural analysis, generalization, systematization, design, and pedagogical experiment. Criteria, indicators and methods for diagnosing the formation of the components of the culture of nature management are revealed. Because of the research, a methodology for the formation of a culture of environmental management in the context of non-formal education was developed, including the goal, content, stages and technology of culturally oriented integral situations. To implement this methodology in educational practice, a program of activities for school “green teams” was developed: “We are in the cultural landscape of estates of our native land”, its purpose, content is revealed, the interconnection of the sections of the program with the technology of culturally oriented integral situations is shown. The results of a pedagogical experiment organized at the experimental sites of Minin University are presented. The results of the experiment, in which 360 high school students took part, made it possible to draw a conclusion about the effectiveness of the formation of a culture of environmental management among students in the context of non-formal education of cultural and ecological orientation.